Difficulties in interpretation of oral food challenge results - Gawryjołek, Julia; Wycech, Alicja; Smyk, Adrianna; Krogulska, Aneta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Oral food challenge is the gold standard in diagnosing food allergies; however, many testing protocols are available. The present article illustrates the difficulties associated with interpreting oral challenge tests with the example of a six-year-old boy with allergy to hen’s eggs. The symptoms observed on the first day of challenge indicated a negative result; however, the consumption of the cumulative dose resulted in anaphylaxis. The interpretation of the oral food challenge can be complicated. The criteria used to determine a positive or negative result are sometimes ambiguous. An accurate interpretation of the results is key to determining correct management in children with food allergy.